2017
DOI: 10.1186/s12938-017-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics study of intra-arterial chemotherapy for oral cancer

Abstract: Background: Intra-arterial chemotherapy (IAC) for oral cancer can deliver a higher concentration of anticancer agent into a tumor-feeding artery than intravenous systemic chemotherapy. However, distribution of anticancer agent into several branches of the external carotid artery (ECA) in IAC has not demonstrated sufficient treatment efficacy. To improve the effectiveness of IAC, the flow distribution of anticancer agent into the branches of the ECA in several IAC methods was investigated using computational fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Other studies reported that mucositis and dysphagia were regarded to be inevitable but reversible 14, 32. Additionally, systemic toxicities such as anemia, thrombocytopenia and leukopenia were also reported before 60-62. Here, we summarized ten toxicities from the 34 studies, including oral diseases, mucositis, leukopenia, dermatitis, anemia, general condition, thrombocytopenia, nausea/vomiting, fever and hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies reported that mucositis and dysphagia were regarded to be inevitable but reversible 14, 32. Additionally, systemic toxicities such as anemia, thrombocytopenia and leukopenia were also reported before 60-62. Here, we summarized ten toxicities from the 34 studies, including oral diseases, mucositis, leukopenia, dermatitis, anemia, general condition, thrombocytopenia, nausea/vomiting, fever and hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…This computational fluid dynamics study was performed based on our previous studies [13,14], and was approved by the Ethics Committee of Yokohama City University (No. B200600075).…”
Section: Methodsmentioning
confidence: 99%
“…where ρ i is the density of the species i. ρ 0 (density of agent) and ρ 1 (density of blood) were set as 1050.0 and 998.2 m 3 /kg [13], respectively. In the 3D region, the viscosity of the mixture was defined using mass-weighted-mixing law as follows:…”
Section: Properties Of Fluidsmentioning
confidence: 99%
See 2 more Smart Citations